Malignant glomus tumor of trachea: a case report with literature review. (January 2016) - Braham, Emna; Zairi, Sara; Mlika, Mouna; Ayadi-Kaddour, Aida; Ismail, Olfa; El Mezni, Faouzi
Glomus tumors of the trachea are extremely rare and generally benign, with very few cases of malignant transformation reported in literature. We present the case of a 74-year-old man explored for cough and dyspnea. Bronchoscopy showed a polypoid mass arising from the posterolateral tracheal wall. Computed tomography demonstrated a mid-tracheal tissular mass obliterating the tracheal lumen. Resection and anastomosis of the trachea were performed. The histological and immunohistochemical findings were consistent with malignant glomus tumor.